Disseminated nontuberculous mycobacteria infection in an immunocompetent host: A case report. Issue 1 (6th January 2023) - Shin, Hye Soon; Yang, Bumhee; Kim, So Rae; Kim, Hee-Sung; Shin, Kyeong Seob; Shin, Yoon Mi
Abstract : Rationale: Disseminated nontuberculous mycobacterial (NTM) infections are rare and occur primarily in immunocompromised hosts. Mycobacterium abscessus complex (MABC), including M abscessus subsp. massiliense (hereafter M massiliense ) is a complex of rapidly growing mycobacterial (RGM) species of NTM. Here, we present a rare case of disseminated NTM infection with RGM bacteremia caused by M massiliense in an immunocompetent host. Patient concerns: A 64-year-old woman with a recent history of spine fracture and septic pneumonia was transferred to our emergency room for dyspnea and fever. A peripherally inserted central catheter (PICC) had been placed over 6 months prior. Diagnoses: Chest computed tomography (CT) showed multifocal patchy consolidations and ground-glass opacity in both lungs. NTM suspected of RGM was isolated from the blood cultures. During hospitalization, multiple erythematous and hemorrhagic crusted nodules developed on the patient's upper and lower extremities, which were confirmed as disseminated NTM infection on skin biopsy. Interventions: After NTM suspected of RGM was isolated from the blood cultures, the patient was empirically treated with antibiotics used for NTM infection, and the PICC was removed. Thereafter, the subspecies of NTM was reported as M massiliense and she was treated according to the antibiotic susceptibility testing results. Outcome: Although skin lesions and inflammatory markers improved gradually during antibiotic treatment over 10 weeks, NTM could still be isolated from the blood culture. Lessons: Disseminated NTM infections with RGM bacteremia in an immunocompetent host have rarely been reported. In this case, PICC placement for more than 6 months was suspected to be an important risk factor for RGM bacteremia in an immunocompetent patient. To date, there are only insufficient case reports, moreover no clear guidelines regarding the optimal choice of antibiotics or length of treatment for disseminated NTM infection. Therefore, it is necessary to establish treatment guidelines for patients with disseminated NTM infection and bacteremia.